THE IMPLEMENTATION OF SIMULATION LECTURE BASED ON THE PRINCIPLE OF NITENI, NIROKKE, NAMBAHI (OBSERVE, IMITATE, INNOVATE) TO IMPROVE THE DISCUSSION SKILLS OF FUTURE MIDDLE SCHOOL TEACHER - Wijayanti, Astuti (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
Teaching needs specific expertise through education and experience. The lecturing unit of Science Teaching is expected able to help future teachers handle the difficulty of implementing their teaching skills of teaching integrated science. Loads of materials can be a guide for the prospective teacher to learn and apply on each component during teaching. Therefore, this research aims to describe the implementation of simulation method based on the principle of niteni (observe), nirokke (imitate), and nambahi (innovate) in improving the discussion skills of future middle school's science teachers. This research is action research. The research occurred in two cycles with students of Integrated Science Education of Universitas Sarjanawiyata Tamansiswa as the object of the research. The finding found that there is an improvement of students' discussion skills from cycle I, 64%, to cycle II, 67%.